ANALISIS KINERJA KARYAWAN DI CV REGAR SPORT KABUPATEN WONOGIRI - Tribun Siti Ambari; Sri Hartono; Sudarwati Sudarwati (ITB AAS INDONESIA Surakarta, 2019)
This study is intended to find the effect of work discipline, motivation and work environment on employee performance at CV REGAR SPORT, Wonogiri Regency. With the random sampling method the respondents used were 60 employees. With multiple linear regression analysis using IBM SPSS statistics 23, the results of the study have a significant effect on work discipline, motivation and work environment on employee performance at CV REGAR SPORT, Wonogiri Regency. There is a significant effect of work discipline on employee performance at the Regar Sport CV and there is an influence but not significant motivation and work environment on employee performance at the CV. Regar Sport. Keywords: discipline, employee performance